4_3 - Section 4.3 Logarithmic Functions Instructor Ms Hoa...

This preview shows pages 1–3. Sign up to view the full content.

Section 4.3: Logarithmic Functions Instructor: Ms. Hoa Nguyen 1 Logarithmic Functions An exponential function y = f ( x ) = a x with a > 0, a 6 = 1 is one-to-one . Then its inverse function f - 1 is the logarithmic function x = f - 1 ( y ) = log a y . In other words, L = R p ⇐⇒ p = log R L . Consequently, we have: log a 1 = 0 because a 0 = 1. log a a = 1 because a 1 = a . Example 1 : Example 2 : 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
f - 1 ( y ) = log a y for all y in the range of f ( x ) = a x . The same as saying: f - 1 ( x ) = log a x for all x in the range of f ( x ) = a x . y = log a x is read as “ y is the logarithm to the base a of x ”. Since the exponential function and the logarithm function are inverses, denote f ( x ) = log a x and f - 1 ( x ) = a x . From Section 4 . 2, we know that: The domain of the exponential function f - 1 is the set of ALL real numbers. The range of the exponential function f - 1 is the set of positive real numbers. Then, what can we say about the domain and range of
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

Page1 / 5

4_3 - Section 4.3 Logarithmic Functions Instructor Ms Hoa...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online